Summer Distribution, Relative Abundance and Encounter Rates of Cetaceans in the Mediterranean Waters off Southern Italy (Western Ionian Sea and Southern Tyrrhenian Sea) - SANTORO, R.; SPERONE, E.; TRINGALI, M. L.; PELLEGRINO, G.; GIGLIO, G.; TRIPEPI, S.; ARCANGELI, A. (Mediterranean Marine Science, 2015)
In summer 2010 and summer 2011, weekly cetacean surveys were undertaken in “passing mode”, using ferries as platform of opportunity, along the “fixed line transect” between Catania and Civitavecchia (Southern Italy). Of the 20 species of cetaceans confirmed for the Mediterranean sea, 8 were sighted within the survey period: 7 species represented by Mediterranean subpopulations (Balaenoptera physalus, Physeter macrocephalus, Stenella coeruleoalba, Delphinus delphis, Grampus griseus, Tursiops truncatus and Ziphius cavirostris) and one considered visitor (Steno bredanensis). We had a total of 220 sightings during the 2010 and a total of 240 sightings in the 2011. The most frequent species was S. coeruleoalba. By the comparison of the data from the two sampling seasons, a significant increase of D. delphis sightings and a decrease of sightings of B. physalus and P. macrocephalus was observed from 2010 to 2011. While all the other species were observed in both sampling seasons, Z. cavirostris and Steno bredanensis were observed only during 2011. The presence of mixed groups of odontocetes was documented too: we sighted groups composed by S. coeruleoalba and D. delphis, by S. coeruleoalba and T. truncatus, and by S. coeruleoalba and G. griseus. The results of this research add useful information on cetacean species in a very poorly known area and highlight the need to standardize large scale and long term monitoring programs in order to detect variation in presence, abundance and distribution of cetaceans populations and understand the effect of anthropogenic factors.